2011
DOI: 10.1071/fp10221
|View full text |Cite
|
Sign up to set email alerts
|

Net carbon exchange in grapevine canopies responds rapidly to timing and extent of regulated deficit irrigation

Abstract: Whole-canopy net CO 2 exchange (NCE C ) was measured near key stages of fruit development in grapevines (Vitis vinifera L. cv. Cabernet Sauvignon) that were managed under three approaches to regulated deficit irrigation (RDI): (1) standard practice (RDI S ), or weekly replacement of 60-70% of estimated evapotranspiration for well watered grapevines; (2) early additional deficit (RDI E ), or one-half of RDI S applied between fruit set and the onset of ripening (veraison), followed by RDI S ; and (3) RDI S follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
29
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 32 publications
9
29
0
1
Order By: Relevance
“…In fact, seasonal canopy WUE of the two treatments provide a very clear-cut picture suggesting that as the water shortage became more severe, canopy WUE markedly decreased. Other studies offering the single-leaf vs. whole-canopy WUE comparison performed in potted (Poni et al, 2009) and field grown vines (Merli et al, 2015;Poni et al, 2014a,b;Tarara et al, 2011) confirmed that, at the canopy level, no gain in WUE was seen under drought.…”
Section: Tablementioning
confidence: 59%
“…In fact, seasonal canopy WUE of the two treatments provide a very clear-cut picture suggesting that as the water shortage became more severe, canopy WUE markedly decreased. Other studies offering the single-leaf vs. whole-canopy WUE comparison performed in potted (Poni et al, 2009) and field grown vines (Merli et al, 2015;Poni et al, 2014a,b;Tarara et al, 2011) confirmed that, at the canopy level, no gain in WUE was seen under drought.…”
Section: Tablementioning
confidence: 59%
“…One of these strategies as discussed before is regulated deficit irrigation, which has been explored to control vegetative growth (Edwards and Clingeleffer 2013; Greven et al 2005;Intrigliolo and Castel 2010;Santesteban et al 2011;Tarara et al 2011;Terry and Kurtural 2011). This technique improves vigor by reducing water application and yield per unit water supply (Acevedo-Opazo et al 2010;Edwards and Clingeleffer 2013;Myburgh 2003;Tarara et al 2011).…”
Section: Effects On Yield Grape and Wine Qualitymentioning
confidence: 99%
“…A recent study performed in different cultivars of grapevine confirmed previous results by showing that there is no consistent correlation between parameters measured at leaf and whole canopy levels . The possible causes of this lack of correlation, explained in detail in different reviews Medrano et al 2012;Schultz and Stoll 2010;Tarara et al 2011;Tomás et al 2014a) are associated to the complexity of the canopy structure, and two physiological mechanisms, leaf night transpiration and plant respiration.…”
Section: Effects On Yield Grape and Wine Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Partial rootzone drying and regulated deficit irrigation were studied in field-grown almond trees by Egea et al (2011) and grapevines by Tarara et al (2011). These studies show the benefits of deficit irrigation techniques in reducing the amount of water used and maximising plant productivity.…”
mentioning
confidence: 99%